Promoting Education and Training as Efforts to Improve Human Resources in African Developing Countries - Muhammad Ridha Iswardhana; Poppy Sulistyaning Winanti; Ririn Tri Nurhayati (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
This research examines training by Indonesia as a form of international assistance and cooperation in Africa. As a new emerging donor, Indonesia wants to assist other countries by formulating mutually beneficial relations among developing countries and gaining a positive image. Indonesia combines training in the form of MRLs and agricultural training in Africa to meet the interests of domestic actors. Domestic politics analysis can explain the role of domestic actors in Indonesia's progress in the international community. This research uses a qualitative explanatory case study method with secondary data from literature studies-furthermore, categorization with Nvivo and theoretical triangulation analysis based on domestic politics analysis and international cooperation and aid. This research found great potential in Africa, which can benefit Indonesia's politics. This training responds to domestic actors' interests and as an expansion effort to expand Indonesian products used globally.